Organized Labour and the Imperial Munitions Board - Bercuson, D. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
The author examines the fight for fair wage clauses in Canadian munitions production at the beginning of this century.